A Bibliometric Analysis on Transformational Leadership - Malodia, Luxmi; Arora, Sudiksha (Gyan Management Journal, 2024)
This paper reveals the literature on transformational leadership. The study  focuses on gathering the information related to the transformational leaders.  The data was collected from 6,090 papers published from 2012 to 2022.  The search items considered the following keywords: “transformational  leadership”, “transformational leader”, “transform leadership”, “transform  leader”. Searching the Scopus database for transformational leadership  titles, abstracts, and author key words yielded a total of 12,874 entries.  Prior to processing the analysis, the author keywords were re-labeled by  making a thesaurus file. The current study has used PRISMA (Preferred  reporting items for systematic reviews and meta- analyses) guidelines  and procedures. This study also focused on how the researches have been  continuously progressing on transformational leadership. Its goal is to  make this topic’s research more visible by showcasing its present features  and providing a thorough and retrospective evaluation of publications.  The study used VosViewer to analyze the collected data.
Keywords: Transformational Leadership; Bibliometric Analysis; Transformational Leader; Transform Leadership